Eksistensi Dewan Pengupahan Dalam Proses Penetapan UpahMinimum - Anas Santoso; Asri Wijayanti (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2020)
An existence of Wage Council in the process of setting minimum wages is currently less than optimal. Thisresearch aimed to analyze the existence of Wage Councils in the process of setting minimum wages based on ananalysis of substance and procedures in legislation. This research was a normative juridical with statuteapproach. The results showed that the differences in the implementation of the provisions of Article 88paragraph (4) of Law 13/2003 with the implementing regulations contained in Article 43 paragraph (1) PP78/2015 jo Keppres 107/2004 jo Article 1 Permenaker 15/2018. The resulting recommendation made a revisionof the rule of law that can optimize the Wage Council's performance in the process of setting minimum wages.